EXPLORING GEOTHERMAL ZONES IN NORTHERN NIGERIA USING LAND SURFACE TEMPERATURE DATA FROM REMOTE SENSING (FUDMA JOURNAL OF SCIENCES, 2025)
Nigeria is still unable to meet even the most basic of its energy needs, this lack of power is most evident in houses located in the North-Central and North-East areas. This paper focused on evaluating geothermal potential through remote sensing techniques in parts of Northern Nigeria. Four digital elevation model (DEM) scenes, three Landsat-9(OLI-2/TIR-2) with minimum zero or minimum cloud cover (280) were identified. The regions around Jibam, Langtang, Aikri, Adikpo, Shemdam, and Ashinge prove to be areas where warm or hot springs can be located.
Keywords: Land Surface Temperature; LandSat-9(OLI-2/TIR-2); MODIS_LST; Lineament density; Warm/hot spring